Hubungan Perencanaan dan Pengarahan Kepala Ruangan dengan Motivasi Kerja Perawat di RS Pameungpeuk Garut Tahun 2017 - Lungguh Perceka, Andhika (Jurnal Ilmiah Administrasi Publik, 2018)
Implementation of good nursing management functions is closely related to the implementation of nursing services. nursing management functions such as planning, organizing, regulating, moving, controlling. Factors affecting the nurse's work motivation are appreciation, growth opportunities, job responsibilities, autonomy, headroom management functions and nurse characteristics. The research method used is descriptive correlation, with 43 sample nurses, data retrieval technique is done by using questionnaire. Based on the results of research from nurses said the planning of the head of the room is not good, some nurses say the direction of headroom is not good, the motivation of some low nurse jobs. Conclusion there is correlation between head room planning with work motivation of nurse and there is correlation of head direction of room with work motivation of nurse at RS Pameungpeuk Garut Year 2017 with P <0,05 (0,004).